Opposites: cars 2 (Disnep UK, 2011)
"Opposites: Cars 2" is a children's book that uses characters and themes from the "Cars" movie to teach about opposites. Through fun illustrations and familiar characters like Lightning McQueen and Mater, the book contrasts concepts such as fast and slow, big and small, or day and night. It's designed to engage young readers while helping them understand the concept of opposites in a playful and interactive way.